Link Between the Conduct as Strategies and Training of Business - G., José; Vargas-Hernández (International Journal For Research In Business, Management And Accounting, 2015)
Industrial systems have received attention in recent years to explain the behavior of companies from a broad perspective, integrating business strategy with structure. Collaborative network is a model that explains the structure of industrial systems to analyze interactions through methods that combine economic with social elements. This paper discusses how partnership strategies of firms derived from external forces to the organization, and implemented by behaviors, shapes the structure, identity and governance of local business networks around a common goal, and highlights the role of agents in the business process evolution of the formalization of networks.